Effect of Return on Equity, and Earnings Per Share Against the Debt to Equity Ratio of Stock Price the Listed Agribusiness Company The Indonesian Stock Exchange Year 2011-2016 - Riana R Dewi, Widya Innanda Sucitra, Suhendro & (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2018)
This study aimed to examine the effect of return on equity (ROE), earnings pershare (EPS) and debt to equity ratio (DER) to the stock price on agribusinesscompanies listed in Indonesia Stock Exchange. Samples were taken from thefinancial statements of listed agribusiness company in the Indonesia StockExchange (BEI) during the period 2011-2016. The sampling method withpurposive sampling method in accordance with the criteria specified. The collecteddata were analyzed using data analysis first conducted classical assumption testbefore hypothesis test. Testing the hypothesis in this study using multipleregression analysis with f test, t test and the coefficient of determination. Theresults of this study showedthat the coefficient of determination obtained a value of0.832, which means that 83.2% of the stock price is affected return on equity(ROE), earnings per share (EPS) debt to equity ratio (DER) of the remaining16.8% is influenced by other variables outside of this research , Hypothesis testresults that return on equity (ROE) and earnings per share (EPS) significantlyaffect the stock price, while debt to equity ratio (DER) did not significantly affectthe stock price,Keywords : ROE, EPS, DER, and stock prices